Sepsis-associated acute respiratory distress syndrome in individuals of European ancestry: a genome-wide association study. Issue 3 (March 2020) - Guillen-Guio, Beatriz; Lorenzo-Salazar, Jose M; Ma, Shwu-Fan; Hou, Pei-Chi; Hernandez-Beeftink, Tamara; Corrales, Almudena; García-Laorden, M Isabel; Jou, Jonathan; Espinosa, Elena; Muriel, Arturo; Domínguez, David; Lorente, Leonardo; et al.
Summary: Background: Acute respiratory distress syndrome (ARDS) is a lung inflammatory process caused mainly by sepsis. Most previous studies that identified genetic risks for ARDS focused on candidates with biological relevance. We aimed to identify novel genetic variants associated with ARDS susceptibility and to provide complementary functional evidence of their effect in gene regulation. Methods: We did a case-control genome-wide association study (GWAS) of 1935 European individuals, using patients with sepsis-associated ARDS as cases and patients with sepsis without ARDS as controls. The discovery stage included 672 patients admitted into a network of Spanish intensive care units between January, 2002, and January, 2017. The replication stage comprised 1345 individuals from two independent datasets from the MESSI cohort study (Sep 22, 2008–Nov 30, 2017; USA) and the VISEP (April 1, 2003–June 30, 2005) and MAXSEP (Oct 1, 2007–March 31, 2010) trials of the SepNet study (Germany). Results from discovery and replication stages were meta-analysed to identify association signals. We then used RNA sequencing data from lung biopsies, in-silico analyses, and luciferase reporter assays to assess the functionallity of associated variants. Findings: We identified a novel genome-wide significant association with sepsis-associated ARDS susceptibility (rs9508032, odds ratio [OR] 0·61, 95% CI 0·41–0·91, p=5·18 × 10 −8 ) located within the Fms-related tyrosine kinase 1 ( FLT1 ) gene, which encodes vascular endothelial growth factor receptor 1 (VEGFR-1). The region containing the sentinel variant and its best proxies acted as a silencer for the FLT1 promoter, and alleles with protective effects in ARDS further reduced promoter activity (p=0·0047). A literature mining of all previously described ARDS genes validated the association of vascular endothelial growth factor A ( VEGFA ; OR 0·55, 95% CI 0·41–0·73; p=4·69 × 10 −5 ). Interpretation: A common variant within the FLT1 gene is associated with sepsis-associated ARDS. Our findings support a role for the vascular endothelial growth factor signalling pathway in ARDS pathogenesis and identify VEGFR-1 as a potential therapeutic target. Funding: Instituto de Salud Carlos III, European Regional Development Funds, Instituto Tecnológico y de Energías Renovables.